Phenol removal from saturated porous media using horseradish peroxidase mediated oxidative polymerization process - Kim, Wongee (Kansas State University, 2007)
Aquifers are frequently contaminated by phenolic compounds from spills, leaking underground storage tanks, or landfills. These compounds can be toxic to a variety of organisms including humans. Their disposal is restricted in many countries with strict limits for acceptable concentrations in drinking water. Phenols that are chlorinated have significantly greater toxicity and are resistant to aerobic biodegradation. Enzyme-mediated in situ stabilization has been advocated as an approach for the treatment of phenolic compounds in soils and groundwater. This research investigated the applicability of a luminol-based chemiluminescence assay to monitor transport of horseradish peroxidase (HRP) enzyme in saturated porous media. The chemiluminescence assay was optimized by varying solution conditions such as the concentration of luminol, p-iodophenol, hydrogen peroxide, ionic strength and pH. All assay components were found to affect the maximum chemiluminescene intensity. The study also evaluated the ability of HRP to mediate the removal of phenol from solution by catalyzing its oxidative polymerization in simulated aquifer conditions. HRP behaved as a conservative tracer in the column packed with Ottawa sand. The concentration of phenol in the column effluent was found to decrease by nearly 90% in the presence of HRP and H2O2 in the continuous flow system. HRP mediated oxidative polymerization of phenols resulted in the production of soluble and insoluble oligomeric products. Modification of porous media caused by the deposition of phenol polymerization products was studied and the impact of media modification on subsequent transport of phenolic contaminants was evaluated using 2,4-dichlorophenol (2,4-DCP) as a probe solute. The pore volume of the porous media was reduced due to the deposition of insoluble phenolic oligomers. The transport behavior of 2,4-DCP showed that the contaminant was retarded in the modified porous media.
Keywords: HRP; Polymerization; Chemiluminescence; Phenol; DCP Transport; Polymer deposition; Engineering, Environmental (0775)